UJI KETAHANAN BERBAGAI VARIETAS TANAMAN KEDELAI (GLYCINE MAX. L) TERHADAP HAMA LAMPROSEMA INDICATA - Muhammad Dirga Patria; Darma Bakti; Ameilia Zuliyanti Siregar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This research aims to determine the resistance of variance of soybean (Glycine max L) varieties to Lamprosema indicata in the field. This research was conducted in Banyumas Village, Stabat sub-district, Langkat Regency, North of Sumatra, from March 2019 until May 2019. This research used by a descriptive method with observational techniques consisting of 15 plots and 225 sample plants. The results of the study showed the resistance and intensity of attacks larvae of L. indicataon leaf of each variety, namely the Dena (average of 10.33 larvae and 24%); followed by Dega consists of 8.17 larvae and 18%, then Detap showed of 6.00 larvae which 12%. Meanwhile, Devon (7.83 larvae and 14%) and Anjasmoro with an average of 7.67 larvae and 13%.Variety of soybean of Data was resilience of attack of L. indicate in the field, while Dena is very susceptible to attack of L. indicate.